Dewey’s Logic: Reviews and Criticisms - Hickman, Larry A. (Analysis. Journal of Philosophical Research, 2022)
I draw attention to some common misunderstandings among Dewey’s critics, as well as to some significant interpretive clarifications by commentators who viewed his work in a positive light. I have found it instructive to look back at two sources as an aid to understanding what his critics found so puzzling about his work. First, there are the reviews in professional journals that appeared in the wake of the publication of the Logic. Second, there are essays by some of his critics included in the Library of Living Philosophers volume published as a part of the celebration of his 80th birthday in 1939. In addition, I occasionally call on ancillary remarks and interpretations from other sources when I think they will help to clarify a point.